Effects of Surfactants and Polyelectrolytes on the Interaction between a Negatively Charged Surface and a Hydrophobic Polymer Surface - Rapp, Michael V (Langmuir : the ACS journal of surfaces and colloids, 2015)
We have measured and characterized how three classes of surface-active molecules self-assemble at, and modulate the interfacial forces between, a negatively charged mica surface and a hydrophobic end-grafted polydimethylsiloxane (PDMS) polymer surface in solution. We provide a broad overview of how chemical and structural properties of surfactant molecules result in different self-assembled structures at polymer and mineral surfaces, by studying three characteristic surfactants: (1) an anionic aliphatic surfactant, sodium dodecyl sulfate (SDS), (2) a cationic aliphatic surfactant, myristyltrimethylammonium bromide (MTAB), and (3) a silicone polyelectrolyte with a long-chain PDMS midblock and multiple cationic end groups. Through surface forces apparatus measurements, we show that the separate addition of three surfactants can result in interaction energies ranging from fully attractive to fully repulsive. Specifically, SDS adsorbs at the PDMS surface as a monolayer and modifies the monotonic electrostatic repulsion to a mica surface. MTAB adsorbs at both the PDMS (as a monolayer) and the mica surface (as a monolayer or bilayer), resulting in concentration-dependent interactions, including a long-range electrostatic repulsion, a short-range steric hydration repulsion, and a short-range hydrophobic attraction. The cationic polyelectrolyte adsorbs as a monolayer on the PDMS and causes a long-range electrostatic attraction to mica, which can be modulated to a monotonic repulsion upon further addition of SDS. Therefore, through judicious selection of surfactants, we show how to modify the magnitude and sign of the interaction energy at different separation distances between hydrophobic and hydrophilic surfaces, which govern the static and kinetic stability of colloidal dispersions. Additionally, we demonstrate how the charge density of silicone polyelectrolytes modifies both their self-assembly at polymer interfaces and the robust adhesion of thin PDMS films to target surfaces